Leveraging industry 4.0 and circular open innovation for digital sustainability: The role of circular ambidexterity - Noor Ul Hadi; Balqees Almessabi; Muhammad Imran Khan (Journal of Open Innovation: Technology, Market and Complexity)
The transition to a circular economy requires a fundamental shift from traditional linear production models to resource efficiency and closed-loop systems. Industry 4.0, with its cutting-edge technologies, has the potential to accelerate digital transformation. However, its impact on digital sustainability is neither automatic nor guaranteed. Many organizations continue to adopt Industry 4.0 technologies to boost their operational efficiency and reduce costs, often failing to align them with circular economy strategies. This study, therefore, delves into the conditional role of circular open innovation in ensuring that digital transformation not only contributes to productivity but also actively fosters circular innovation and digital sustainability. To explore this, the study adopts a conceptual methodology and develops a theoretical framework grounded in a synthesis of recent scholarly literature on Industry 4.0, circular ambidexterity, and circular open Innovation. The literature-based findings suggest that circular open innovation plays a critical enabling role by facilitating cross-sector collaboration, knowledge-sharing, and co-creation, allowing organizations to fully capitalize on Industry 4.0 for circular transitions and sustainable transformation. The study also found that organizations with high circular open innovation engagement integrate open innovation platforms, blockchain-enabled supply chain transparency, and AI-driven circular analytics, leading to scalable circular business models. In contrast, those that fail to engage in circular open innovation may use Industry 4.0 solely for efficiency gains, missing opportunities to create truly regenerative systems. This study highlights that integrating Industry 4.0 with circular open innovation is crucial to achieving circular transformations and ensuring digital technologies contribute meaningfully to sustainable outcomes.